Development of a Simulation Program to Determine the Performance of Gas Turbine - Elsaied, Waiel Kamal (2008)
The efficiency and power output of a gas turbine plant depend on the temperature of inlet air. At high ambient temperature, the power output and efficiency of a gas turbine decrease, with significant increase in specific fuel consumption. Analytical models were developed to describe the behavior of the gas turbine cycle, such as power output, efficiency, specific fuel consumption and heat rate. These models were then implemented using Matlab. The results from the computer simulation were compared to operation data of power output, efficiency, specific fuel consumption and heat rate. It was found that the analytical models were able to reproduce similar trends of behavior as the operation trends. These indicate that the analytical models can be used to investigate the perfromance of the gas turbine under various operating conditions.